Effect of educational intervention on improving nurse's general health in military hospitals of Iran: a quasi-experimental study - Vahid Ranaei; Fatemeh Kalroozi; Mojtaba Sadeghi; Soudabeh Yarmohammadi; Kristin Haglund; Nahid Mehrabi (BMC, 2022)
Abstract Background Nursing in military hospitals affects their general health. Educational interventions can help to maintain the general health of nurses. This study aimed to evaluate the effect of an educational intervention to improve the general health of nurses in military hospitals. Methods In this quasi-experimental study, 146 nurses working in military hospitals in Tehran, Iran in 2021 were included in the study. The one-month educational intervention included videos, pamphlets, and motivational messages about promoting general health. General health questionnaire with 28 items (GHQ28) was study tool. The allocation of nurses to groups was not random, it was based on personal interest. Frequency (percentage), and mean (standard deviation) were used to describe, and the chi-square test, Fisher's exact test, independent and paired t-test were used for data analysis. All analyzes were performed in SPSS 24 software with a significance level of 5%. Results A total of 146 nurses participated in the study, most of them were in the age group of 30 to 40 years (64 people, 43.8%), and 76.7% (112 people) of them were women. The results of the independent sample t-test showed after the intervention, general health scores in the intervention group had a significant decrease compared to the control (p < 0.001) (change in intervention group = -31.1, V.S change in control = 0.55). The results of paired t-test showed that only in the intervention group, the value of the general health score and its dimensions were significantly different (p < 0.001). Conclusions The educational intervention performed well and decreased the score of the general health of military nurses. Given that these positive effects may be temporary, it is necessary to design and perform educational interventions over a longer period.